VERBA FRASAL DALAM NOVEL THE STARS SHINE DOWN KARYA SHIDNEY SHELDON - Mawikere, Michael Frisky (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI)
ABSTRACT Â  ThisÂ  researchÂ  entitled â€œPhrasalÂ  VerbsÂ  inÂ  theÂ  novelÂ  â€œTheÂ  StarsÂ  ShineÂ  Down byÂ  SidneyÂ  Sheldonâ€Â  isÂ  writtenÂ  toÂ  identifyÂ  andÂ  analyzeÂ  theÂ  phrasalÂ  verbsÂ  inÂ  termsÂ  ofÂ  formÂ  andÂ  meaning. TheÂ  methodÂ  usedÂ  isÂ  descriptiveÂ  method.Â  TheÂ  dataÂ  areÂ  takenÂ  fromÂ  theÂ  novel,Â  andÂ  analyzed Â basedÂ  onÂ  theÂ  conceptÂ  ofÂ  BeaumontÂ  danÂ  GringerÂ  inÂ  termsÂ  ofÂ  formÂ  andÂ  ThomsonÂ  MartinetÂ  forÂ  theirÂ  meanings. TheÂ  writerÂ  findsÂ  thatÂ  thereÂ  areÂ  fourÂ  formsÂ  ofÂ  phrasalÂ  verbsÂ  inÂ  theÂ  novel, thoseÂ  areÂ  the first formÂ  : verb + particle +,Â  the second form : verb + particle + object andÂ  verb + object + particle,Â  the tirth formÂ  : Verb + Particle + ObjectÂ  inÂ  whichÂ  verbÂ  cannotÂ  beÂ  separatedÂ  fromÂ  theÂ  particle,Â  and the fifth form : Verb + Particle + Preposition. TheÂ  writerÂ  alsoÂ  findsÂ  thatÂ  thereÂ  areÂ  phrasalÂ  verbsÂ  thatÂ  have Â moreÂ  thanÂ  oneÂ  meaningsÂ  thoseÂ  are getÂ  up,Â  putÂ  down,Â  comeÂ  back,Â  talkÂ  about,Â  comeÂ  up,Â  finishÂ  up,Â  keepÂ  up, Â makeÂ  up,Â  putÂ  up,Â  turnÂ  up, setÂ  ofÂ  andÂ  giveÂ  up. ThisÂ  researchÂ  couldÂ  helpÂ  theÂ  readerÂ  toÂ  increaseÂ  theÂ  knowledgeÂ  especiallyÂ  on phrasalÂ  verbsÂ  andÂ  toÂ  understand phrasal verb in the novel The Stars Shine Down deeply. Â  KeyÂ  words : English phrasal verb,Â  TheÂ  StarsÂ  ShineÂ  Down.